THE ISSUE OF DIALECTICAL BALANCE BETWEEN KNOWLEDGE, POWER, AND MORALITY IN THE EPIC “SADDI ISKANDARIY” (International journal of artificial intelligence, 2026)
This scholarly article examines the issue of dialectical balance between knowledge, political power, and morality in Saddi Iskandariy, the concluding epic of Alisher Navoi’s Khamsa. Based on the artistic and philosophical interpretation of the image of Iskandar (Alexander), the study reveals Navoi’s concept of the ideal ruler. Through an analysis of the epic, the role of knowledge as the guiding force of authority and morality as its limiting and regulating principle is substantiated. Special attention is paid to the issues of justice, responsibility, and spiritual perfection within the context of Eastern political and philosophical thought.